Enzyme activity in germinating seeds of winter soft wheat when the light regime changes due to UV seed radiation - E. N. Simonova; N. S. Kravchenko (Зерновое хозяйство России)
One of the main environmental factors occurring if the integrity of the ozone layer is violated, is natural ultraviolet radiation, which affects plant organisms in the natural environment. In plant breeding in order to stimulate seed germination, mercury-quartz lamps, such as BNPO 2-30-001U3.5 can be used as artificial sources. The article shows that UV treatment of seeds causes changes in the growth and morphogenesis of plants. Ultraviolet radiation, as any stress factor, causes adaptation, including changes in physiological and biochemical processes, as well as an increase of enzymes activity. Stimulation during seed germination, which accelerates seed growth and foliage development, includes electrophysical methods, in particular, seed treatment with ultraviolet radiation. The environmental safety of such technologies makes them relevant and in great demand in agricultural production. The use of a BNPO 2-30-001U3.5 mercury-quartz lamp to stimulate physiological and biochemical processes in germinating seeds made it possible to identify the morphological differences of sprouts, various enzyme activity depending on the exposure time during irradiation. After the seeds had been irradiated with a BNPO 2-30-001U3.5 mercury-quartz lamp, they were soaked in distilled water, and amylase and scavenger enzyme activity was determined during swelling and sprouting. During the experiment, there were identified optimal modes of seed UV irradiation. Laboratory germination of seeds treated with UV radiation for 3-5 minutes ranged from 4 to 11%.